Global Supply Chains and Trade Policy - Blanchard, Emily J.; Bown, Chad P.; Johnson, Robert C. (World Bank, Washington, DC, 2016)
How do global supply chain linkages modify countries' incentives to impose import protection? Are these linkages empirically important determinants of trade policy? To address these questions, this paper introduces supply chain linkages into a workhorse terms-of-trade model of trade policy with political economy. Theory predicts that discretionary final goods tariffs will be decreasing in the domestic content of foreign-produced final goods. Provided foreign political interests are not too strong, final goods tariffs will also be decreasing in the foreign content of domestically-produced final goods. The paper tests these predictions using newly assembled data on bilateral applied tariffs, temporary trade barriers, and value-added contents for 14 major economies over the 1995-2009 period. There is strong support for the empirical predictions of the model. The results imply that global supply chains matter for trade policy, both in principle and in practice.